Enforcement Quandary in Maritime Crimes: Espousing the Tangle of Prescriptive Jurisdiction - Abdulrazaq O. Abdulkadir (Fakultas Hukum Universitas Lampung, 2023)
It is inconceivable to have crimes without laws created prescribing or enforcing them. There must also be in existence a concomitant authority, either a state or an institution vested with the capacity to enforce these laws. In cases those crimes that occur on land, it is usually straightforward to determine the body vested with the legal power to prescribe and enforce these claims. Through qualitative and quantitative sampling, this study argues that for crimes that occur on the sea; territorial, internal or high seas, determining the state with jurisdiction is not so clear. This is because there is the possibility that various states could have competing rights to prescribe, adjudicate and enforce criminal laws in relation to a criminal offense. It is therefore important that a survey of these competing/concurrent rights of states be carried out. This research also investigates whether, by international law, these rights are actually concurrent or whether one is superior to the other. It also carried out an assessment of how the concurrent rights of states are exercised and how conflicts are resolved when they occur. The research founds that in real terms, one should be superior to the others and not so concurrent.